SCIENTIFIC AND PRACTICAL FUNDAMENTALS OF CABBAGE GROWING TECHNOLOGIES IN REPEATED CROPS WHITEBUSH (Brassica Capitata Lizg) - Alisher Juraboevich Shokirov (Galaxy International Interdisciplinary Research Journal, 2023)
In re-sowing, the profitability of the hybrids of white cabbage "Geant" f1, "Kozak" F1 and "W 61-19" F1 were 24.1, 20.0 and 23.1% higher, respectively, compared with the standard variety "Sharkia-2". when planting varieties "Sharkia-2" and Saratoni according to the scheme 90x30 cm. the yield was higher in the variety "Sharkia-2" by 20.8%, and in the variety "Saratoni" by 19.6% compared to the variety "Sharkia-2". the control variant is 70х40 cm. when planting seedlings of varieties "Sharkia-2" and "Saratoni" on june 15, the yield was 112.6% for the variety "Sharkia-2" and 104.0% for the variety saratoni compared to the control (30.vi). When fertilizing at the rate of N250 P150 K100 kg/ha, the yield of the Sharkia-2 variety was 121.4%, and the yield of the Saratoni variety was 116.6% compared to the control. Compared with the control, with an increase in soil moisture before watering (60%) to 90%, the yield was - 119.1-161.6% for the Saratoni variety and -113.7-147.3% for the Sharkia-2 variety.